Pioneers and paradigms in sprint science: a thematic historical mini review - Li, J.; Xiao, X.; Fan, Y. (Frontiers in Sports and Active Living, 2026)
This mini review traces the historical evolution of sprint science by examining the pivotal contributions of key figures across interconnected disciplines. Focusing on thematic developments, this paper investigates how physiological foundations, biomechanical analysis, strength theory, quantitative approaches, and applied coaching practice have collectively shaped the discipline. Specifically, this synthesis highlights the physiological bioenergetics mapped by Archibald Vivian Hill, the foundational coaching methodologies of Sam Mussabini and Clyde Hart, the kinematic and biomechanical innovations of Ralph Mann and Richard Neil Hinrichs, the quantitative strength theories of Vladimir Mikhailovich Zatsiorsky, and the ground reaction force paradigms established by Peter Weyand. By chronologically synthesizing these advancements, the review illustrates that the maturation of sprint science did not follow a singular linear trajectory. Instead, the field emerged through the complex, synergistic integration of diverse knowledge domains. Ultimately, this synthesis suggests that future advancements in sprint science will depend upon the continued cross-pollination of these disciplines, particularly through the potential adoption of AI-driven models of data analysis to optimize performance outcomes and establish a more rigorous, evidence-based scientific framework.